Protein Profile of Tissue Culture of TRI2025 Tea Clone - Eskundari, Ratna Dewi; Taryono, Taryono; Indradewa, Didik; Purwestri, Yekti Asih (Biosaintifika: Journal of Biology & Biology Education, 2019)
Tea is well known as favourite healthy drink for almost all people over the world. Tea propagation using conventional and modern ways are now developing rapidly. However, information regarding the protein profile of tissue culture of tea plant has not been revealed yet. This study aimed to determine the difference of protein profile of tea’s tissue culture using SDS-PAGE. This study was conducted using embryonic axes of TRI2025 tea clone cultured on MS media supplemented with 2,4-D for inducing somatic embryogenesis and globular-like structure (GLS) regeneration, and MS media supplemented with BAP for inducing shoot via organogenesis. The results revealed that proteins in the size of 37.69; 54.89; 60.77; 71.35; 87.34; and 92.99 KDa might be involved at somatic embryogenesis, and about 38.69 KDa, 69.27 KDa, and 55.76 KDa respectively for GLS, initiation of shoot, and initiation of GLS derived leaf. Predicted key protein for leaf initiation both directly or through GLS was about 31-33 KDa, while for callusing were about 27.56 and 52.73 KDa, and constitutive protein was about 22.75 KDa. This study provides the first report of protein profile of tea’s tissue culture. The information obtained can be beneficial as a marker for explant for somatic embryogenesis, GLS, or organogenesis pathway and as a scientific information for further biotechnology development.